PERAN GURU DALAM MEMBENTUK KARAKTER PEDULI LINGKUNGANPADA SISWA KELAS III DI MIS TARBIYAH TEBAS TAHUN PELAJARAN 2024-2025 - Mimi; Suriadi; Astaman (JIP: Jurnal Ilmu Pendidikan, 2026)
This research began with the identification of a problem in Grade III at MIS Tarbiyah Tebas regarding the formation of students’ environmental care character. The objectives of this study are to: (1) analyze the teacher’s strategies in shaping students’ environmental care character in Grade III at MIS Tarbiyah Tebas in the 2024–2025 academic year; (2) identify the supporting and inhibiting factors affecting the teacher’s success in developing students’ environmental care character in Grade III at MIS Tarbiyah Tebas in the 2024– 2025 academic year; and (3) examine the impacts influencing the formation of students’ environmental care character in Grade III at MIS Tarbiyah Tebas in the 2024–2025 academic year. This study employed a qualitative approach with a descriptive research design. Data collection techniques included interviews, observations, and documentation. The data analysis techniques consisted of data collection, data reduction, data display, and conclusion drawing. The validity of the data was ensured through source triangulation and member checking. The results of the study indicate that: (1) The teacher implemented various active strategies in shaping students’ environmental care character, such as integrating environmental values into classroom learning, involving students directly in cleaning activities, and providing good role models. (2) Supporting factors included parental involvement and support from the school principal, while inhibiting factors included students’ lack of knowledge. (3) The impacts observed were increased student awareness in maintaining cleanliness and caring for the environment, as well as their ability to apply these values in daily life.